Oncological and Functional Outcomes of Transoral Robotic Surgery and Endoscopic Laryngopharyngeal Surgery for Hypopharyngeal Cancer: A Systematic Review - Lai, Katherine W. K.; Lai, Ronald; Lorincz, Balazs B.; Wang, Chen-Chi; Chan, Jason Y. K.; Yeung, David C. M. (Frontiers in Surgery, 2022)
Objectives Hypopharyngeal carcinoma (HPC) is a head and neck carcinoma with poor prognosis. Traditional laryngopharyngectomy offered promising oncological outcomes at the cost of functional outcomes. The recent advent in transoral robotic surgery (TORS), an organ-preserving surgery, has opened up new perspectives in the treatment for HPC. Here, we evaluate minimally invasive organ preservation surgery [TORS and endoscopic laryngopharyngeal surgery (ELPS)] for HPC in terms of feasibility and oncological and functional outcomes. Methods This is a systematic review. Six databases [CUHK Full-Text Journals, Embase 1910 to 2021, Ovid Emcare, Ovid MEDLINE (R), CINAHL, PubMed] were searched for articles and primary studies for TORS and ELPS for HPC. Screening was completed using predefined inclusion or exclusion criteria. Results A total of 8 studies on TORS and 3 studies on ELPS were eventually chosen after full-text review. For studies on TORS, 61.3% of patients (84 out of 137) still survived at the last follow-up with a mean follow-up time of 23.20 months (range: 12.8–37.21 months). Severe intraoperative and postoperative complications have not been reported. No cases of TORS required a conversion to open surgery. Swallowing function was optimal postoperatively with only 6 patients eventually required a percutaneous endoscopic gastrostomy (PEG) for feeding. Disease-specific survival was taken as the parameter for the measurement of oncological outcomes. A total of 2 studies reported a disease-specific survival of 100% within their follow-up period of 1 and 1.5 years, respectively. Another 2 studies reported a 2-year DSS of 89 and 98%, respectively. A 5-year DSS of 100% in early stage and 74% in late stage were achieved in one study. Another study also reported a 5-year DSS of 91.7%. For studies of ELPS, a 5- and 3-year disease-specific survival of 100% were achieved in 2 studies. Patients who underwent ELPS had good postoperative swallowing function with no PEG placement. There were also no other fatal complications. Conclusions Both TORS and ELPS for HPC provide satisfactory long-term oncological and functional outcomes improving postoperative quality of life of patients.